Constituent Recall Arrangements of the People's Representative Board - Reni Putri Anggraeni; Ahmad Alveyn Sulthony Ananda; Elliot Gross (Jurnal Kajian Pembaruan Hukum, 2024)
The principle of popular sovereignty is fundamental in establishing a democratic legal state, primarily reflected in general elections that determine representatives in the People's Representative Council (DPR). However, this principle often loses its significance post-election, as citizens have little control over their elected representatives. This is evident in the DPR's Inter-Time Change (PAW) mechanism, which excludes public participation. This study emphasizes two main points: the urgent need to amend Article 22B of the 1945 Constitution and to develop a new DPR reconstruction model as part of legal reform. Employing normative legal research through statutory, comparative, and case approaches, the study analyzes secondary legal materials. The findings reveal that the nomenclature of Article 22B requires revision to facilitate greater public involvement in the DPR dissolution process. Currently, dissolution relies on political party leaders, leading members to prioritize party interests over public aspirations, which can create conflicts. The article's language should be amended to allow for public dismissal of DPR members through a clearly defined legal mechanism. Additionally, the study suggests that the PAW process in Indonesia could draw inspiration from the Philippines and Venezuela, incorporating public input through a withdrawal proposal and voting mechanism for council members, thus reinforcing popular sovereignty in the legislative process.